Placenta Accreta Spectrum Disorder, Risk Factor, Clinical Grading, Histopathology, and Diagnostic Ultrasound - Khudadad, Sarah Khadim; Al-Haidari, Taghreed Khalil (Journal of Science in Medicine and Life, 2025)
Background: Placenta accreta spectrum (PAS) is a serious pregnancy condition that can result in maternal morbidity and mortality due to hemorrhage. Prenatal diagnosis is based on subjective interpretation of sonographic findings, but the definitive diagnosis can only be made clinically at delivery and confirmed by histopathology. Aim of the study: To elucidate the risk factors, clinical grading, histopathology correlations and diagnostic accuracy of perinatal imaging in pregnancies complicated by PAS disorders. Patients and methods: A prospective cohort study that was conducted in the department of Obstetrics and Gynecology at Al- Elwiyah Maternity Teaching Hospital during a period of 12 months from 1st of January 2022 to 31st of December 2022. The study included all cases of PAS disorders according to the ultrasonic features presented to our hospital during the study period. Results: Seventy-three cases were enrolled with finding of ultrasonic features suggestive of PAS disorders. All participants underwent C/S at which only 47 cases were diagnosed as having PAS disorders depending on clinical features, of those 41 cases underwent hysterectomy and histopathological diagnosis showed different grades of PAS in 37 cases only. Cases of PAS disorders had higher mean maternal age, higher gravidity, parity, and higher rate of previous C/S. Placental hypervascularity was significantly associated with clinical PAS diagnosis. The ultrasound features were not sensitive nor specific in diagnosing PAS according to clinical and histological findings, but ultrasonic features associated with high PPV in cases of those who had PAS disorders and required hysterectomy. Conclusion: Ultrasound had limited sensitivity and specificity but was associated with high PPV making it a good tool for screening for PAS disorders. Advancing maternal age, high parity, high miscarriage rate associated with increased risk of PAS disorders. •The clinical diagnosis associated with high specificity and strongly associated with histopathologic finding.